Determinants of household recycling - Pavlinović Mršić, Slađana (Array, 2020)
A case of managing a public utility in post-transitional context is elaborated in this paper. The aim is to identify main determinants of household recycling, in order to make recommendations for design of appropriate recycling policy in Split (Croatia). Based on the overview of relevant literature, individual motivation towards waste selection is explored and preliminary survey results are presented. Implications for local policy-making and management of local public utilities are discussed.